(untitled) (Global Journal of Management and Business Research, 2013)
Retirement is perceived as a threat to many employees rather than an issue of interest. The objective of this research is to explore the concept of retirement, ways through which employees can prepare towards retirement and the post-retirement strategies. Both secondary and primary data was used in the study. Survey research method was adopted. Disproportional stratified sampling method was adopted in selecting the sample. Simple percentages and the chi-square statistical test were used for data analysis. The study concludes that pension reform in Nigeria is faced with many challenges, which includes, coverage, adequacy, administrative efficiency, transparency, corruption, governance and regulation. The study also recommends that the financial, regulatory and legal framework should be strengthened and consolidated and that qualified persons and organizations should do the actual management of the pension system so that the challenges and problems of pension administration in Nigeria will be eliminated.